17 Heritability Estimate of Heart Score. (22nd October 2022) - Kukor, Isabella; Enns, R Mark; Thomas, Milton G; Holt, Timothy N; Cleveland, Matthew; Holland, Ben P; Word, Alyssa B; Ellis, Guy
Abstract: Feedlot heart disease (FHD), also known as bovine congestive heart failure, affects feedlot cattle at low to moderate elevations. This disease can cause feedlot death and preliminary research suggests unfavorable influences on performance and carcass quality in those individuals reaching their harvest endpoint. The severity of FHD for an individual animal at harvest can be determined by a heart scoring system that ranges from 1 to 5 corresponding to the increasing degree of heart failure with a score of 1 a normal heart and larger scores indicative of increased malformations. Heart scores (HS) are collected on individual animals at harvest. Previous research indicated that differences exist between sires as to their progeny's propensity for developing FHD as indicated by HS of 3, 4 and 5. As a result of these sire differences, the objective of this study was to estimate heritability of HS obtained from a group of fattened feedlot cattle. Heart scores, numbers of cattle (Grade 1: 290 ; Grade 2: 728; Grade 3: 340; Grade 4: 64; Grade 5: 0) pedigree, and feedlot pen information were collected from 1, 422 individual animals. The pedigree used in the evaluation consisted of the 1, 422 individuals and 89 unique sires. No dam information was available on the scored animals. Heritability was estimated using a mixed effect animal model and the statistical software package ASReml 3.0. Fixed effects included scorer, sex, and kill age. Sex was not found to be significant in the model. Individual animal was included as the sole random effect. Scorer (P < 0.05) and kill age (P < 0.1) were found to influence variability in heart score, although kill age was detected as a tendency (P = 0.07). The heritability of HS was estimated to be 0.27 ± 0.10. The genetic variation was 0.15 and the phenotypic variation in the model was 0.40. These results suggest, HS is moderately heritable and has the potential to respond to genetic selection.